THE ROLE OF CHARACTER EDUCATION IN STRENGTHENING TOLERANCE ATTITUDES AMONG STUDENTS AT PONDOK PESANTREN NURUL ISLAM PROBOLINGGO - Istifaur Rosidah (PT. Education Research Center, 2025)
This study aims to explore the pivotal role of character education in fostering tolerance among students (santri) at Pondok Pesantren Nurul Islam, Probolinggo, Indonesia. In the context of globalization marked by rapid social transformations and heightened cultural diversity character education emerges as a critical foundation for shaping individuals capable of embracing and respecting differences. The research examines the specific strategies and pedagogical methods employed by the pesantren to instill tolerance as a core value, and investigates their influence on the moral and social dispositions of the students. Adopting a qualitative research approach, the study employed in-depth interviews with both educators and students, allowing for rich, contextual insights into the lived experience of character formation within the pesantren environment. Findings reveal that Pondok Pesantren Nurul Islam has successfully embedded tolerance into its educational framework through a variety of initiatives, including leadership training, community service projects, and interfaith dialogue forums. These programs transcend mere academic instruction by nurturing ethical awareness, empathy, and constructive social engagement. The integration of such values not only strengthens interpersonal harmony within the pesantren community but also contributes to the broader aim of cultivating a tolerant and cohesive society. This research offers valuable implications for educational institutions seeking to design and implement character education strategies that effectively respond to the challenges of cultural pluralism in the modern era.